La responsibilidad por daño ambiental - Femenías S., Jorge A. (Ediciones Universidad Católica de Chile, 2017)
This book analyzes the legal nature, limits and extension of the liability regime for environmental damage enshrined in Law No. 19,300 on General Bases of the Environment (LBGMA), in light of the examination of the principles that inform environmental law. This work is undoubtedly an obligatory reference for the ministers of the superior courts of justice, of the environmental courts and for the lawyers who litigate before these magistracies, as well as for all scholars of environmental law, a discipline that becomes more and more criticism and that until now had not had a work of these characteristics.